LATIHAN INCLINE PUSH-UP DAN CLAP PUSH-UP DAPAT MENINGKATKAN POWER LENGAN PADA ATLET TARUNG DERAJAT - Jamaludin, Jamaludin (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
Arm power is a part of physical condition that is widely used when fighting in a degree of combat sports, therefore arm power must receive special attention when undergoing training or preparation before fighting. The problem that arose in the MAN2 Selong East Lombok satlat was the lack of attention to the training of lenga power by the trainer, the wrong paradigm between arm strength training and arm power. The objectives to be achieved in this study are to increase arm power with incline push-up exercises (push-ups on the bench) and clep push-ups (hand push-up push-ups). The method used in this study is an experimental method with a two group pre test post test design. The samples in this study were 20 combatants fighting athletes (units of training) MAN2 Selong East Lombok, which amounted to 20 people, where the sample was divided into two, namely the first 10 people were given incline push-up training (bench push-ups) and The second 10 were given clep push-up exercises (hand patted push-ups). The instrument used to measure arm power is the "Hand Medicine Ball Put" and data analysis techniques using the t test using SPSS 16.0. The results of this study are based on data obtained in the field is that there are differences in the effect of incline push-up exercises (push-ups on the bench) and Clap Push-ups (Push-up Pat) on arm power in degree combat athletes at MAN 2 Selong, Lombok Regency East 2019, from the two types of exercises above the Clap Push-up exercise (Push-up Pat) has a better effect compared to the incline push-up exercises (push-ups on the bench)